Straight from the source's mouth: Controls on fieldconstrained sediment export across the entire active Corinth Rift, central Greece - Watkins,SE; Whittaker,AC; Bell,RE; Brooke,SAS; Ganti,V; Gawthorpe,RL; McNeill,LC; Nixon,CW (Basin Research, 2020)
The volume and grainsize of sediment supplied from catchments fundamentally control basin stratigraphy. Despite their importance, few studies have constrained sediment budgets and grainsize exported into an active rift at the basin scale. Here, we used the Corinth Rift as a natural laboratory to quantify the controls on sediment export within an active rift. In the field, we measured the hydraulic geometries, surface grainsizes of channel bars and fullweighted grainsize distributions of river sediment at the mouths of 47 catchments draining the rift (constituting 83% of the areal extent). Results show that the sediment grainsize increases westward along the southern coast of the Gulf of Corinth, with the coarsefraction grainsizes (84th percentile of weighted grainsize distribution) ranging from approximately 19 to 91 mm. We find that the median and coarsefraction of the sieved grainsize distribution are primarily controlled by bedrock lithology, with late Quaternary uplift rates exerting a secondary control. Our results indicate that grainsize export is primarily controlled by the input grainsize within the catchment and subsequent abrasion during fluvial transport, both quantities that are sensitive to catchment lithology. We also demonstrate that the median and coarsefraction of the grainsize distribution are predominantly transported in bedload; however, typical sandgrade particles are transported as suspended load at bankfull conditions, suggesting disparate sourcetosink transit timescales for sand and gravel. Finally, we derive both a full Holocene sediment budget and a grainsizespecific bedload discharged into the Gulf of Corinth using the grainsize measurements and previously published estimates of sediment fluxes and volumes. Results show that the bedload sediment budget is primarily comprised (~79%) of pebble to cobble grade (0.475–16 cm). Our results suggest that the grainsize of sediment export at the rift scale is particularly